Teoria da justiça distributiva e sua aplicabilidade pelo supremo tribunal federal na declaração de constitucionalidade da contribuição previdenciária pelos servidores públicos inativos - Fonseca, Alessandra Miriam Francischetti Ribeiro da (Universidade do Vale do Rio dos Sinos, 2012)
Theory of Distributive Justice: the topic being addressed in this research focuses on investigating the applicability of distributive justice in the Supreme Court in the declaration of the constitutionality of social security contributions for retired civil servants, pointing out discrepancies between theoretical currents communitarians and individualists. Identify the contribution from jusfilosófico, the constitutional interpretation of the Supreme Court values driven by the application of distributive justice in this case on the basis of solidarity principiológico, striking feature of the communitarian paradigm inaugurated by the 1988 Constitution, the fundamental objective of establishing democratic state to build a free, fair and inclusive.
Keywords: Communitarian paradigm; Social security contribution of civil servants retired; Solidarity; Democratic state of law; Distributive justice; Paradigma comunitarista; Contribuição previdenciária dos servidores públicos inativos; Solidariedade; Estado democrático de direito; Justiça distributiva; ACCNPQ::Ciências Sociais Aplicadas::Direito